Evaluation of four bioestimulantes and three sustrates in the propagation of Vallea stipularis L.f. - Rosero, Sonia; Erazo, Norma; Guallpa, Miguel; Usigña, Marlene (Enfoque UTE, 2017)
The research consisted in evaluating four biostimulants and three substrates for the propagation of Vallea stipularis L.f. in greenhouse conditions. The biostimulants corresponded to: plant hormone rooting (B1), agrohormones 10-10-10 (B2), ESPOCH biostimulant (B3) and Gron Gibb (B4). The substrates consisted of: 50% black soil + 25% peat + 25% sand (S1); 50% black soil + 25% peat + 25% humus (S2) and 50% peat + 50% humus (S3). For the study, it was used a randomized complete design (RCD) with factorial arrangement, it was determined the coefficient of variation and the Tukey test at 5% for the separation of means. The application of the biostimulants in the substrates was done at the time of planting. According to the results obtained, the best biostimulants corresponded to B1 (plant hormone rooting), applied in the seeds for 15 minutes, with which the highest emergency percentage was obtained (70.96%); with biostimulant B2 (agrohormones 10-10-10), applied for five minutes it was obtained 70.67% and with B3 (Gron Gibb) 70.37%. The best substrate for emergence of plants was: 50% peat + 50% humus) with 73.67% of emergence, where the highest plant height and root length were achieved, instead, the ESPOCH biostimulant (microoganisms) reported a 67, 11% emergency.